High-temperature oxidation of novel stainless steels developed using high-entropy alloy design concepts - Passos, João Gabriel da Cruz (2025)
Recent studies on High-entropy Alloys (HEAs) and HEA-based alloys found promising property combinations. One branch of this field investigates the gap between HEAs (equiatomic or quasi-equiatomic compositions) and conventional alloys (one main element). Conventional stainless steels, which already have multiple main elements (Fe, Ni, Cr) are prime candidates for this investigation. In this work, multicomponent stainless steels were developed in search of compositions resistant to high-temperature oxidation. At first, promising multicomponent alloys found in the literature were chosen and slightly altered according to the objectives of this study. The as-cast alloys were exposed to high-temperature oxidation tests and microstructural characterization. All oxidized samples in this study were characterized by X-ray diffraction and a scanning electron microscope equipped with energy dispersive X-ray spectroscopy detector (SEM-EDX). SEM-EDX was also used in polished cross-sections to analyze the oxide layer. The same techniques were used to characterize the as-cast microstructure. Some samples were further characterized with electron probe microanalysis (EPMA) and Raman spectroscopy. The initial oxidation tests showed, for example, that Cu was very detrimental to oxidation resistance, whereas Si was essential. Based on the results and on the composition of conventional alloys, a mixture experiment was developed. In this experiment, a base Fe-Cr-Ni-Co-Si alloy was defined and the content of Al and Mo varied according to the experimental design, for a total of seven compositions. These alloys were subjected to microstructural characterization as well as cyclic and isothermal oxidation tests between 800 and 1100 °C. No interesting interactions between Al and Mo were identified, leading to the reduction of the experimental field to three compositions called B, A and M (base alloy, base alloy with 2.5 at.% Al and base alloy with 2.5 at.% Mo, respectively), as well as a reference alloy (AISI 310). The composition of the novel alloys was quantified through optical emission spectroscopy (OES). They were exposed to thermogravimetric analysis (100 h) and long-term isothermal tests (1000 h) at 900 °C under air and air + 5 vol.% water vapor atmospheres. The results led to the conclusion that alloy A was significantly more oxidation-resistant than AISI 310 and had a higher resistance to sigma phase formation. The alloy A had a significantly reduced amount of nonprotective spinel containing Fe and Ni in its oxidation layer and was more resistant to spallation thanks to the presence of a semi-continuous Al oxide layer below the chromia layer. It also gained much less mass than the other alloys, with a parabolic coefficient two orders of magnitude lower than the other alloys. Alloys B and M were less resistant, but still yielded better results than the AISI 310. Finally, samples of alloy A were coated with Al (forming a 100 m-thick coating) and Cr through pack cementation and subjected to the water vapor test. The coatings were not resistant, significantly oxidizing and spalling. In general, the selection process was successfully applied, resulting in the promising alloy A. Some phenomena, such as the severe oxidation of the Al-rich coat and the effect of water vapor on sigma phase stability are interesting extra results of the research, and are still being investigated.